2021
DOI: 10.1136/bmjopen-2020-041579
|View full text |Cite
|
Sign up to set email alerts
|

Group practice impacts on patients, physicians and healthcare systems: a scoping review

Abstract: ObjectiveTo identify the advantages and disadvantages that group practices have on patients, physicians and healthcare systems.Study designA scoping review was performed based on the methodology proposed by Arksey and O’Malley, and refined by Levac et al. Titles and abstracts were screened by two reviewers. A quantitative analysis was performed to assess the type, year and region of publication, as well as the population studied. A qualitative descriptive analysis was performed to identify common themes.Study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 76 publications
1
23
0
Order By: Relevance
“…2 Amsterdam Public Health Research Institute, Amsterdam, the Netherlands. 3 Research Department of Medical Education, University College London, London, UK. 4 Amsterdam University Medical Centers, Vrije Universiteit Amsterdam, University of Amsterdam, Amsterdam, Netherlands.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…2 Amsterdam Public Health Research Institute, Amsterdam, the Netherlands. 3 Research Department of Medical Education, University College London, London, UK. 4 Amsterdam University Medical Centers, Vrije Universiteit Amsterdam, University of Amsterdam, Amsterdam, Netherlands.…”
Section: Discussionmentioning
confidence: 99%
“…Governments in high-income countries are reforming healthcare systems to achieve high quality and safe care while maintaining costs [ 1 , 2 ]. To meet reconfigurations demands, self-employed physicians reorganise themselves into new and often larger organisations, impacting their work environment and practice [ 3 7 ]. Self-employed physicians may find that by reorganising, they gain control over their work, allocate resources more efficiently [ 5 ], or create a strong collective that may offer more power to negotiate with hospitals [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This can be interpreted as a sign of a PM’s positive effect on the personal time and efficiency gains for physicians. Nevertheless, it also emphasizes the need for interpersonal relationship management and managerial tasks in larger practices [ 10 , 13 , 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…An international scoping review found that while group practices improve physicians’ quality of life, the higher stress caused by the more complex interpersonal/staff relationships is a disadvantage [ 25 ]. In a German context, it was confirmed that burnout in joint practices was higher than in solo practices [ 30 ].…”
Section: Discussionmentioning
confidence: 99%